Clinical profile and outcomes of rejection after deep anterior lamellar keratoplasty in keratoconus - Priyanka Sudaboina; Sunita Chaurasia; Somasheila Murthy (Indian Journal of Ophthalmology)
Purpose: To report the clinical features and management outcomes of rejection after deep anterior lamellar keratoplasty (DALK). Methods: The clinical features, indications, predisposing risk factors, management, and outcome of six eyes of six patients with rejection after DALK were analyzed retrospectively. Results: The median time of rejection from the day of surgery was 12 (range 3–36) months. Median duration of symptoms was 4 (range 2–28) days. The indication for DALK was keratoconus in all eyes. The clinical features at presentation included graft haze, vascularization, and melt at the graft–host junction. The risk factors noted were noncompliance to steroids in all eyes, vernal conjunctivitis (four eyes), and eccentric graft (one eye). The rejection episode reversed with topical steroids in all eyes and intravenous methylprednisolone in one eye. One eye developed secondary fungal keratitis after initial recovery and one eye had a second episode of rejection 3 months later, which resulted in progressive vessels and lipid keratopathy in the visual axis. The median best corrected visual acuity was 20/40 (range 20/30–20/200). Conclusion: Severe stromal rejection can present with graft melt. Repeat episodes of rejection can occur on sudden cessation of topical steroids. Prompt recognition of clinical signs and symptoms with timely management helps in quick reversal of the rejection episode. Reversal of graft rejection results in good visual outcomes.